Rural Marketing For-FMCG - Arul Kumar, S.; Madhavi, C. (Indian Journal of Marketing, 2006)
Today economy is conformed to two major and far-reaching changes - a change form domestic to global and a change from when to rural. Both these changes are evolutionary. Corporate sector has already realized the vast opportunities. Existing in the rural sector and are trying to harness these with their strategies specially aimed at rural markets. Marketing in rural areas needs altogether different strategy as against the marketing in urban area and the psyche entirely from the of when consumer. Addressing certain issues pertaining to rural marketing. This paper aims at exploring the consumer behavior patterns of rural consumers with reference to FMCG product of tooth paste, shampoo and toilet soap.